Chapter Introduction - Beynon-Jones, Siân M. (Taylor & Francis, 2019)
In bringing together this collection on law's relationship with time, our concern has been to register an increasing commitment among scholars across disciplines to shift such patterns of engagement. Our own research over the past few years has been preoccupied with the question of law's temporalities, drawing on a range of critical resources to investigate, through empirical research, the coproduction of legal and temporal norms, subjectivities and political ontologies. In our related efforts to create an interdisciplinary network of scholars working on law and time,2 we have noted a distinct openness to questions of law, regulation and legality from social sciences and humanities scholars working on temporality, on the one hand (e.g. Adkins, 2012; Amoore, 2013; de Goede, 2015; Mitropoulos, 2012; Opitz et al., 2015), and an incisive conceptual and methodological interdisciplinarity among critical and socio-legal scholars, on the other (e.g. Cooper, 2013; Cornell, 1990; Craven et al., 2006; Douglas, 2011; Fitzpatrick, 2013; Keenan, 2014; Philippopoulos-Mihalopoulos, 2013; Valverde, 2015; van Marle, 2003). Critical approaches to linear time and attention to law's shaping of time in diverse forms and through multiple techniques have animated research across disciplines. We hope that the present collection will highlight these shared concerns, fostering the cross-fertilisation of ideas and methods and further developing conversations on law and time between socio-legal scholars, anthropologists, sociologists, geographers, historians and others.